Tracing attribute and scope of research and applied projects in Africa's water energy food nexus implementation: A review. Issue 136 (October 2022) - Muhirwa, Fabien; Shen, Lei; Elshkaki, Ayman; Velempini, Kgosietsile; Hirwa, Hubert
Abstract: The importance of integrating water, energy, and food (WEF) resource management into nexus approach has been widely recognized. However, despite its rapid growth, there are little discussion of the knowledge transfer from nexus research to practice of WEF nexus implementation in Africa. This research examines the WEF nexus implementation baseline through critical analysis of present studies and official project reports initiated by African government institutions from 2011 to 2021. The findings indicate that numerous WEF nexus research projects in Africa focus on generating fundamental knowledge with limited practice. Indeed, among the 237 WEF-related applied projects analyzed, only 26 projects correspond to the nexus approach in three resource sectors. Many proposed projects are managed at the level of individual resource areas and are prioritized according to urgent needs or regional contexts rather than being integrated for mutual benefit. The word "production" receives a high score in the statistics of term frequency and inverse document frequency (TF-IDF), expressing that it is considered very relevant in the process of implementing the nexus approach. The results of the similarity index between the content messages of the academic articles and the project implementers' reports show a low similarity score of 0.25, indicating some imbalance in understanding and adapting nexus concepts between these two critical sectors. Hence, reflecting on the various nexus opportunities reviewed in this study, such as Bonn nexus conceptions and projects allocation, may serve as a focal point and assist WEF nexus implementers, particularly scholars, in resolving the numerous ambiguities that exists in WEF nexus research and practice. Highlights: The study analyses WEF nexus conception principles that support SDGs implementation. Policymakers and researchers interpret nexus concepts in different ways. WEF projects are more prioritized at the sectoral level. Action research is well recommended in implementing the WEF nexus approach.